{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

cardinality

# cardinality - Cardinality The"cardinality of a set provides...

This preview shows pages 1–2. Sign up to view the full content.

Cardinality The “cardinality” of a set provides a precise meaning to “the number of elements” in the set, even when the set contains infinitely many elements. We start with the following very reasonable definitions of “the set S contains the same number of elements as the set T ”, “the set S contains fewer elements than the set T ” and “the set S contains more elements then the set T ”. Definition 1 Let S and T be nonempty sets. Then card ( S ) = card ( T ) ⇐⇒ there exists an f : S T which is one–to–one and onto card ( S ) card ( T ) ⇐⇒ there exists an f : S T which is one–to–one card ( S ) card ( T ) ⇐⇒ there exists an f : S T which is onto card ( S ) < card ( T ) ⇐⇒ card ( S ) card ( T ) but card ( S ) 6 = card ( T ) card ( S ) > card ( T ) ⇐⇒ card ( S ) card ( T ) but card ( S ) 6 = card ( T ) Definition 2 Let S be a nonempty set. Then (a) The set S has card ( S ) = n IN if card ( S ) = card ( { 1 , 2 , 3 , · · · , n } ) . (b) The set S is countable if card ( S ) card (IN). The set S is countably infinite if card ( S ) = card (IN). (c) The set S is uncountable if it is not countable. (d) The set S has the cardinality of the continuum if card ( S ) = card (IR). We now verify that and , in the sense of cardinality, work as expected. Proposition 3 Let S , T and U be nonempty sets. Then (a) card ( S ) card ( T ) if and only if card ( T ) card ( S ) . (b) Either card ( S ) card ( T ) or card ( S ) card ( T ) . (c) If card ( S ) card ( T ) and card ( S ) card ( T ) , then card ( S ) = card( T ) . (d) If card ( S ) card ( T ) and card ( T ) card ( U ) , then card ( S ) card ( U ) . Proof: (a) If card ( S ) card ( T ), then there is a one–to–one function f : S T . Fix any s 0 S . Then g ( t ) = f - 1 ( t ) if t is in the range of f s 0 otherwise maps T onto S , so that card ( T ) card ( S ). If card ( T ) card ( S ), then there is a function g that maps T onto S . So the sets g - 1 ( s ) = t T g ( t ) = s , s S are disjoint and nonempty. For each s S select one t s g - 1 ( s ). Then f ( s ) =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}